Triterpenoids From Kadsura coccinea With Their Anti-inflammatory and Inhibited Proliferation of Rheumatoid Arthritis-Fibroblastoid Synovial Cells Activities - Yang, Yu-pei; Jian, Yu-qing; Liu, Yong-bei; Ismail, Muhammad; Xie, Qing-ling; Yu, Huang-he; Wang, Bin; Li, Bin; Peng, Cai-yun; Liu, Bin; Man, Rong-yong; Wang, Wei (Frontiers in Chemistry, 2021)
One new 3,4-seco-17,13-friedo-lanostane triterpenoid heilaohuacid A (1), one new 3,4-seco-17,14-friedo-lanostane triterpenoid heilaohuacid B (2), five new 3,4-seco-lanostane triterpenoids heilaohuacids C-D (3–4) and heilaohumethylesters A-C (7–9), one new 3,4-seco-cycloartane triterpenoid heilaohuacid E (5), and one new intact-lanostane triterpenoid heilaohuacid F (6), together with twenty-two known analogues (10–31), were isolated from heilaohu. Their structures were determined using HR-ESI-MS data, 1D and 2D NMR spectra, 13C NMR calculations, and electronic circular dichroism (ECD) calculations. Heilaohuacids A and B (1 and 2) contain a 3,4-seco ring A and unprecedented migration of Me-18 from C-13 to C-17 or C-14 to C-18. This type of lanostane triterpenoid derivatives was rarely reported so far. More importantly, all compounds against inflammatory cytokines IL-6 and TNF-α levels on LPS-induced RAW 264.7 macrophages were evaluated, and compounds 4 and 31 significantly inhibited the release level of IL-6 with IC50 values of 8.15 and 9.86 μM, respectively. Meanwhile, compounds 17, 18, and 31 significantly inhibited proliferation of rheumatoid arthritis-fibroblastoid synovial (RA-FLS) cells in vitro with IC50 values of 7.52, 8.85, and 7.97 μM, respectively.